Effect of supplemental potassium and buffer in starters for early-weaned calves - P. Flynn; J.L. Morrill; P.G. Reddy; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1987)
Sixty Holstein heifers were used from birth to 8 weeks of age to study the effect of amount of potassium (K) in the diet and of adding a buffer to the starter. Starters were formulated with and without 1% trona, a natural ore buffer, at K concentrations of .9, 1.25, and 1.5% of the dry matter. To supply adequate fiber, yet allow formulation of the starter containing .9% K, 20% prairie hay was included. All calves were fed milk and a prestarter, using an early weaning procedure. Growth and feed consumption data and evaluation of health and metabolic activity were used as response criteria. Overall, calves fed 1.25% K consumed the same amount, whether fed buffered or nonbuffered starter. At other K levels, calves fed nonbuffered starters consumed more. Growth of calves fed buffered starter with 1.5% K was depressed. Metabolic data supported the conclusion that this buffer was not beneficial with this type of starter. Increasing the amount of K did not significantly increase calf response, but there was a trend for gains to increase as K increased to 1.25% in both buffered and nonbuffered starters. Since these calves were not heat stressed, opportunity for maximum benefit from added K did not exist.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Potassium; Weight gain; Feed consumption; Fecal consistency